Environmental circadian disruption suppresses rhythms in kidney function and accelerates excretion of renal injury markers in urine of male hypertensive rats - Hill, Atlantis M. (Am J Physiol Renal Physiol, 2021)
Nontraditional work schedules, such as shift work, have been associated with numerous health issues, including cardiovascular and metabolic disease. These work schedules can chronically misalign environmental timing cues with internal circadian clock systems in the brain and in peripheral organs, leading to dysfunction of those systems and their associated biological processes. Environmental circadian disruption in the kidney may be an important factor in the increased incidence of hypertension and adverse health outcomes in human shift workers. The relationship between renal rhythmicity and injury resilience is not well understood, especially in the context of environmental, rather than genetic, manipulations of the circadian system. We conducted a longitudinal study to determine whether chronic shifting of the light cycle that mimics shift work schedules would disrupt output rhythms of the kidney and accelerate kidney injury in salt-loaded male spontaneously hypertensive, stroke-prone rats. We observed that chronic shifting of the light-dark (LD) cycle misaligned and decreased the amplitude of urinary volume rhythms as the kidney phase-shifted to match each new lighting cycle. This schedule also accelerated glomerular and tubular injury marker excretion, as quantified by nephrin and KIM-1 compared with rats kept in a static LD cycle. These data suggest that disrupted rhythms in the kidney may decrease resilience and contribute to disease development in systems dependent on renal and cardiovascular functions.